Sodium chloride methanol solution spin-coating process for bulk-heterojunction polymer solar cells - 刘统方 胡煜峰 邓振波 李熊 朱丽杰 王越 吕龙锋 王铁宁 娄志东 侯延冰 滕枫 (Chinese physics B, 2016)
The sodium chloride methanol solution process is conducted on the conventional poly（3-hexylthiophene）（P3HT）/[6,6]-phenyl-C61-butyric acid methyl ester（PC_（61）BM） polymer bulk heterojunction solar cells. The device exhibits a power conversion efficiency of up to 3.36%, 18% higher than that of the device without the solution process. The measurements of the active layer by x-ray photoelectron spectroscopy（XPS）, atomic force microscopy（AFM）, and ultraviolet photoelectron spectroscopy（UPS） indicate a slight phase separation in the vertical direction and a sodium chloride distributed island-like interface between the active layer and the cathode. The capacitance–voltage（C–V） and impedance spectroscopy measurements prove that the sodium chloride methanol process can reduce the electron injection barrier and improve the interfacial contact of polymer solar cells. Therefore, this one-step solution process not only optimizes the phase separation in the active layers but also forms a cathode buffer layer, which can enhance the generation, transport, and collection of photogenerated charge carriers in the device simultaneously. This work indicates that the inexpensive and non-toxic sodium chloride methanol solution process is an efficient one-step method for the low cost manufacturing of polymer solar cells.